miRNAs in Pericardial Fluid and their role in Cardiac Fibrosis: Conversations inside us and how they change our hearts - Costa, Francisco Ribeiro Coelho Melo (2021)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia